2017
DOI: 10.1515/pdtc-2016-0031
|View full text |Cite
|
Sign up to set email alerts
|

Building a Living, Breathing Archive:A Review of Appraisal Theories and Approaches for Web Archives

Abstract: Abstract:The paper provides a review of published literature on the collection and development of Web archives, focusing specifically on the theories, techniques, tools, and approaches used to appraise Web-based materials for inclusion in collections. Facing an enormous amount of Web-based materials, archival institutions and other cultural heritage institutions need to devise methods to actively select Webpages for preservation, creating Web archives that constitute a cultural record of the Web for the benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The study conducted by Post (2017) found that national archives through enactment of the National Archives Act are to collect archival material as part of preserving cultural heritage. The collection of ERMS requires collaborative collective models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study conducted by Post (2017) found that national archives through enactment of the National Archives Act are to collect archival material as part of preserving cultural heritage. The collection of ERMS requires collaborative collective models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While it is democratic in nature, the web is large with often undefined boundaries that must be viewed within context. A single website, removed from this interconnectedness, loses its context and value, unlike discrete digital files which have set parameters and established best practices for preservation [7]. In theory, a user types or selects a URL and is taken to that website, but, all too often, in practice, the published content at that web address has either changed or no longer exists.…”
Section: Archiving the Fragile And Abundant Internetmentioning
confidence: 99%
“…Regarding appraisal theories, Post (2017) argues that active selection of webpages by heritage institutions is necessary, in addition to verifying when new approaches are required. As it is impossible to preserve the entire web, it is necessary to consider the characteristics of web materials including which websites are appropriate to the collection, how frequently they are collected and how much of existing material to capture.…”
Section: Background and Related Workmentioning
confidence: 99%